Using “Listening Time Podcast” on Spotify to Improve Students’ Listening Comprehension - Masbirorotni; Failasofah; Izzah, Nurul (Universitas Sulawesi Barat, 2023)
This pre-experimental study investigates whether the use of “Listening Time Podcast” on Spotify is able to improve students’ listening comprehension. It was conducted at class R002 which consisted of 29 students. They were the students of English Department, Universitas Jambi academic year 2022/2023. The data was gathered through pre-test and post-test. The findings of the study show that the mean score for post-test is higher than the post-test score. The mean score for pre-test was 59.72 while the post-test score was 73.24. This result indicates that there is an increase in the student's listening ability after they were taught by using the Listening Time podcast on the Spotify application. Comparison of the mean score of pretest and post-test by conducting a T-test paired sample T-test shows the result of the significance value (2-tailed) was 0.001 < 0.005. This means that H0 hypothesis is rejected and H1 is accepted.